METHODS OF REVEALING OF DISCONTINUITY FLAWS AND CONTROL OF THE CAST IRONS STRUCTURE USING BODY AND HEAD WAVES - A. R. Bajev; G. E. Konovalov; A. L. Majorov; M. V. Asadchaja; M. A. Tishchenko (Литьë и металлургия)
The problems of structure-and defectoscopy of cast irons by supersonic method are examined. The new principle schemas of ultrasonic measurings, constructions of acoustic transformers are presented and their analysis is carried out. The results of investigation of influence of graphite form on speed of ultrasound are given and also some peculiarities the surface und subsurface faults reveal by shadow way.